P064 Audit of post-exposure prophylaxis with associated risk profiles at the gay men's health services, dublin, 2016. (8th June 2017) - Moloney, Geraldine; O'Dea, Siobhan; O'Sullivan, Colm; Clarke, Susan
Abstract : Introduction: The incidence of HIV infection is rising in Ireland, reaching a rate of 10.6/100, 000 people in 2015. MSM is the most common route of transmission, reported as 50.9% of new diagnoses. There is a comparative surge in requests for HIV post-exposure prophylaxis (PEP) in Gay Men's Health Services (GMHS), Dublin: 44% increase in 2016, vs. 2015. In 2016, a PEP proforma was devised for consistent clinical assessment of PEP requests and decisions. Methods: We performed a retrospective review of all PEP requests from June-December 2016, following the introduction of this proforma. We investigated exposure types, reported use of condoms, alcohol, drugs, and partners STI status. We assessed appropriateness of PEP decisions in accordance with national guidelines, and compared risk profiles to published findings from 56 Dean Street. Results: 116 PEP assessments occurred in this time, with the specific proforma. All were evaluated as appropriate for PEP. GMHS attendees had same median age (31 years) as those of Dean Street. However, GMHS attendees reported significantly elevated risks of no condoms used (73 vs 54%; p <0.0001), more recreational drugs (30 vs 20%; p = 0.01), with an additional 13% using both drugs and alcohol. GMHS attendees reported more IAI, and significantly less group sex activity (3.5 vs 11%; p =0.02). Partner's viral or bacterial STI status was rarely known. Discussion: PEP is appropriately assessed and provided for GMHS attendees. High risk sexual behaviours are common, requiring comprehensive HIV prevention strategies for the continuing epidemic.